Assessment of music experience after cochlear implantation: A review of current tools and their utilization - Tiffany P. Hwa (KeAi Communications Co., Ltd., 2021)
Objective: To provide an overview of the current available music assessment tools after cochlear implantation (CI); to report on the utilization of music assessments in the literature; to propose potential future directions in music assessment after CI. Methods: A thorough search was performed in PubMed, Embase, and The Cochrane Library through October 31, 2020. MeSH search terms, keywords, and phrases included “cochlear implant,” “cochlear prosthesis,” “auditory prosthesis,” “music,” “music assessment,” “music questionnaire,” “music perception,” “music enjoyment, and “music experience.” Potentially relevant studies were reviewed for inclusion, with particular focus on assessments developed specifically for the cochlear implant population and intended for widespread use. Results/conclusions: Six hundred and forty-three studies were screened for relevance to assessment of music experience among cochlear implantees. Eighty-one studies ultimately met criteria for inclusion. There are multiple validated tools for assessment of music experience after cochlear implantation, each of which provide slightly differing insights into the patients’ subjective and/or objective post-activation experience. However, no single assessment tool has been adopted into widespread use and thus, much of the literature pertaining to this topic evaluates outcomes non-uniformly, including single-use assessments designed specifically for the study at hand. The lack of a widely accepted universal tool for assessment of music limits our collective understanding the contributory and mitigating factors applicable to current music experience of cochlear implantees, and limits our ability to uniformly evaluate the success of new implant technologies or music training paradigms.